Mineralogy, geochemistry and economic potentialities of heavy mineral sand resources of Bangladesh (Journal of Nepal Geological Society, 2019)
Heavy mineral sand deposits are the important mineral resources of Bangladesh. Systematic mineral exploration activities carried out in the south eastern coastal belt of Bangladesh were successful to discover seventeen heavy mineral sand (HMS) deposits in the coastal beach and off-shore islands. Mineralogy, geochemistry and mineral processing characteristics of the heavy mineral sands and their economic potentialities are presented in the present paper. On an average, HMS deposits contain 23% total heavy minerals. In heavy fraction, average weight percentage of the economic minerals is: zircon 4.20%, rutile 2.04%, ilmenite 26.03%, garnet 6.45%, kyanite 3.92%, leucoxene 2.30%, magnetite 1.87% and monazite 0.31%; and the average weight percentage of other non-economic heavy minerals is 53.88%. Heavy mineral sand deposits altogether contain 1.76 million tons of economically important heavy minerals which are: limonite (1,025,000 tonnes), garnet (223,000 tons), zircon (158,000 tonnes), leucoxene (97,000 tons), kyanite (91,000 tons), rutile (70,000 tons), magnetite (81,000 tones) and monazite (17,000 tonnes). Occurrence of large amount of economic heavy minerals in the sand bars of Brahmaputra-Jamuna River has been reported by some recent studies. On an average, total heavy mineral percentage of the Brahmaputra-Jamuna sand bars is around 8.92%. Mineral sand processing on the bulk samples has been carried out at the pilot plant comprising gravity, magnetic and electrostatic separators to characterize the separation characteristics of individual economic heavy minerals. Geochemical studies on the separated heavy minerals show that TiO2 in rutile is around 90% and ZrO2 in zircon is around 65%, which are quite satisfactory in respect of commercial grade. Ilmenite contains low level of titanium dioxide (TiO2-43%) and higher level of chromium, manganese and iron. Beneficiation and upgrading of limonite will be required to make it a market able commodity. Valuable minerals present in the heavy mineral sand deposits of Bangladesh need to be mined sustainably and utilized for the benefit of the country.